Newly Qualified Female Teachers' Perception of Teaching Practicum as a Component of Initial Teacher Education in South Africa - Charmaine Helena Iwu (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
This study was undertaken with the aim of understanding how newly qualified female teachers perceive teaching practicum in the South African context. Teaching Practicum is a vital component of the initial teacher education (ITE) programme because it enriches future teachers' knowledge, skills and abilities towards a lifelong career in the teaching profession. Teachers make valuable contributions to the growth of any nation as they help produce future leaders. It is therefore necessary to have a competent teaching workforce to improve pass rates as well as reduce dropout rates among learners. The study took the qualitative deductive premise making use of semi-structured interviews to collect data from more than 30 novice teachers. Key words, which helped in the identification of themes, were distilled from the responses. A core overall finding of the study point to a mix of experiences - benefits and shortcomings - which not only affect the development of prospective teachers but also have profound implications for both policy enhancement and implementation. Regarding policy enhancement and implementation, it is suggested that universities and schools where novice teachers are posted for teaching practice should have good relations for support advancements. In this case, it is advised that the novice teachers should be exposed to critical mentoring opportunities to allow for clearer understanding of the real classroom scope. This study believes that for this to be fruitful, schools should among others be well-equipped. Suggestions for further research are also flagged. .